Making Additional Food to Prevent Stunting from Sago Flour (Metroxylon sp), Sea Grapes (Caulerpa sp), and Mackerel (Rastrelliger sp.) in Hoat Sorbay District, Southeast Maluku Regency - Waranmasebule, Celcius; Latar, Dullah Irwan; Hanoatubun, Marthinus I.H. (Jurnal Ar Ro'is Mandalika (Armada), 2025)
This community service activity aims to empower mothers in Hoat Sorbay District, Southeast Maluku Regency, in preventing stunting in children through the production of additional food based on local food ingredients, namely sago flour (Metroxylon sp), sea grapes (Caulerpa sp.), and mackerel (Rastrelliger sp.). The methods used include interactive counseling and practical training in making additional food to prevent stunting with an educational and participatory approach. Participants are actively involved in direct practice in making nutritious additional food using easily obtained local ingredients. The main results of the activity showed a significant increase in the knowledge and skills of participating mothers about the importance of balanced nutrition and the use of local food as an effort to prevent stunting. Pre-test and post-test evaluations showed a decrease in the low knowledge category from 60% to 12%, and an increase in the high knowledge category from 20% to 40%. In addition, this activity encourages the use of economical local resources, strengthens social solidarity among mothers, and opens up opportunities for food diversification and small businesses based on local products. The positive impact of this activity is increasing public awareness of nutrition, independence in providing nutritious food, and contribution in reducing the risk of stunting in the target area. This activity is expected to be a model for developing a sustainable stunting prevention program and can be replicated in other areas with similar conditions.